NAFKAH DALAM KONTEKS HUKUM ISLAM - Idin, Andi Muhammad; Mustaming, Mustaming (UIN Palopo, 2023)
The purpose of writing this journal is to find out the concept of nafkah in Islam as well as the scope of legal aspects that govern, and its implications in everyday life. The research method in this study uses This type of research is descriptive qualitative using a literature study approach (Library Research). Library studies describe theoretical analysis, scientific studies, references, and literature related to local community habits, norms, and values that are built on the observed field conditions. With the method of collecting data and facts of information and exploring the sources contained in journals and scientific papers, encyclopedias, literature, and other data sources related and relevant to the topic, the formulation of the concept of Maqasid sharia in sharia retail marketing management can be formed through pre-existing theories. The research results in this study show that the concept of nafkah in Islam is not only about providing material needs but also includes broader aspects of life. The husband as the head of the family has a responsibility to his wife and children, a husband has obligations that Allah has set, including the rights of his wife and children that must be fulfilled, including the obligation to provide maintenance. The nafkah agreed upon by Islamic jurists is nafkah which is mentioned in the nash-nash syar'i and is a primary need in life for the wife. Understanding and implementing this concept is expected to improve the welfare of the people and strengthen the foundation of family life.